DEVELOPMENT AND PERFORMANCE EVALUATION OF POLYSULFONE/POLYDIMETHYLSILOXANE COMPOSITE MEMBRANE FOR CO2/CH4 SEPARATION UNDER WET CONDITIONS - SULEMAN, MALIK SHOAIB (2018)
Membrane technology in gas separation has gained importance due to several advantages over other separation techniques. Despite of the good performance offered by polymeric membranes, the commercial application of polymeric membranes is limited due to the swelling in polymeric membranes caused by humid feed.